Invasive seaweeds transform habitat structure and increase biodiversity of associated species. (24th April 2017) - Dijkstra, Jennifer A.; Harris, Larry G.; Mello, Kristen; Litterer, Amber; Wells, Christopher; Ware, Colin
Summary: The visual landscape of marine and terrestrial systems is changing as a result of anthropogenic factors. Often these shifts involve introduced species that are morphologically dissimilar to native species, creating a unique biogenic structure and habitat for associated species within the landscape. While community‐level changes as a result of introduced species have been documented in both terrestrial and marine systems, it is still unclear how long‐term shifts in species composition will affect habitat complexity or its potential to influence the biodiversity of species that occur at the base of the food web. We analysed quadrat photos collected at several subtidal sites in the Gulf of Maine over a 30+ year period, and collected individual seaweed species to determine their complexity and the biodiversity of meso‐invertebrates associated with each species. By coupling the relationship of 30+ years of shifts in seaweed assemblages, morphological structure of the seaweed assemblage, and their meso‐invertebrates, we determined introduced seaweeds have increased by up to 90%, corresponding to a rise in two‐dimensional (2D) structure, and a decline in canopy height of subtidal rocky habitats. The highly complex two‐dimensional habitat provided by introduced filamentous red seaweeds supports two to three times more meso‐invertebrate individuals and species that form the base of the food web than simpler forms of morphological habitat. Synthesis . The present study demonstrates a long‐term shift in foundation species towards a dominance of invasive seaweeds that directly reduce canopy height and increase the 2D biogenic structure of the habitat. These introduced seaweeds harbour greater biodiversity of species found at the base of the food web than seaweeds with simpler forms such as the native kelp species. Such shifts in habitat structure will propagate to food webs by influencing the structure of lower trophic‐level meso‐invertebrates and indirectly upper trophic‐level species that feed on these invertebrates and use the seaweed structure as refuge. Abstract : The present study demonstrates a long‐term shift in foundation species towards a dominance of invasive seaweeds that directly reduce canopy height and increase the 2D biogenic structure of the habitat. These introduced seaweeds harbour greater biodiversity of species found at the base of the food web than seaweeds with simpler forms such as the native kelp species. Such shifts in habitat structure will propagate to food webs by influencing the structure of lower trophic‐level meso‐invertebrates and indirectly upper trophic‐level species that feed on these invertebrates and use the seaweed structure as refuge.